Using XML data integration and ontology reuse to share agricultural data. (2nd June 2009) - Sall, Ousmane; Lo, Moussa; Gandon, Fabien; Niang, Cheikh; Diop, Ibrahima
We present a data integration approach to enable multi-agency partners to share their agricultural data sources. We perform the integration in three phases. First, a structural integration phase, based on the use of XML documents warehouses (called dataweb), allows to create a warehouse for each partner. A second step consists in the integration of these dataweb by associating an ontology-based knowledge to each warehouse. That is done by a semi-automatic building of OWL ontology starting from dataweb and by re-use of the Agricultural Ontology Service. A third mediation phase permits to query in a uniform manner these different semantic dataweb.